2021
DOI: 10.13057/biodiv/d221004
|View full text |Cite
|
Sign up to set email alerts
|

Crustacean and mollusk species diversity and abundance in the mangrove communities of Mimika District, Papua, Indonesia

Abstract: Abstract. Setyadi G, Rahayu DL, Pribadi R, Hartati R, Wijayanti DP, Sugianto DN, Darmawan A. 2021. Crustacean and mollusk species diversity and abundance in the mangrove communities of Mimika District, Papua, Indonesia. Biodiversitas 22: 4146-4157. A mangrove crustacean and mollusk species diversity study was carried out in four mangrove estuaries in Mimika District, Papua, Indonesia. Two locations were selected on each estuary; for each location, samples of crustaceans and mollusks were collected from 5 m × 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 26 publications
0
14
0
2
Order By: Relevance
“…In the estuary area, including the mangrove, the Decapoda richness in Siombak Lake is higher than the Western area of Segara Anakan Lagoon at 17 species (Rimadiyani et al 2019). However, this is lower than the 103 species found in the Mimika mangrove area (Papua) (Rahayu and Setyadi 2009), the 19 species of Decapoda found in Purworejo mangrove area (Wiryanto et al 2017), the 38 species of decapod found in s in Lasongko Bay, Southeast Sulawesi, (Hamid and Wardiatno 2018), 21 species in degraded mangrove area at Tanjung Panjang Nature Reserve in Gorontalo (Lapolo et al 2018), and the 41 species of crustaceans found in the mangrove area of Mimika, Papua (Setyadi et al 2021).…”
Section: Richness and Composition Of Crustaceansmentioning
confidence: 86%
See 1 more Smart Citation
“…In the estuary area, including the mangrove, the Decapoda richness in Siombak Lake is higher than the Western area of Segara Anakan Lagoon at 17 species (Rimadiyani et al 2019). However, this is lower than the 103 species found in the Mimika mangrove area (Papua) (Rahayu and Setyadi 2009), the 19 species of Decapoda found in Purworejo mangrove area (Wiryanto et al 2017), the 38 species of decapod found in s in Lasongko Bay, Southeast Sulawesi, (Hamid and Wardiatno 2018), 21 species in degraded mangrove area at Tanjung Panjang Nature Reserve in Gorontalo (Lapolo et al 2018), and the 41 species of crustaceans found in the mangrove area of Mimika, Papua (Setyadi et al 2021).…”
Section: Richness and Composition Of Crustaceansmentioning
confidence: 86%
“…Studies on crustaceans (Decapoda) related to spatial and temporal distribution in estuary and mangrove ecosystems have been widely conducted. For example, several studies related to crustaceans (Decapoda) in the estuary and mangrove ecosystems include the composition of crab species (Decapoda: Brachyura) in Lombok Island (Murniati 2015); the biodiversity of aquatic organisms (including crustaceans) in Purworejo (Central Java) (Wiryanto et al 2017); diversity of decapod crustaceans in Lasongko Bay, Southeast Sulawesi (Hamid and Wardiatno 2018); in degraded mangrove area at Tanjung Panjang Nature Reserve in Gorontalo (Lapolo et al 2018), andSetyadi et al (2021) conducted documentation of crustaceans and mollusks in the mangrove area of Timika, Papua.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, crustacean samples were taken once in September. Sampling took place during daylight hours at low tide, using a hand shovel to excavate crustacean burrows and blood cockles at depths of 10-20 cm in each research plot (Setyadi et al 2021). All samples collected at the research locations were placed in sample bottles and fixed with 4% formalin, then transported to the University Samudra Biology Laboratory for identification, based on morphological similarities among crustacean species, including color, body size, legs and claws shapes, and various other morphological features (Ginantra et al 2023;WoRMS 2024).…”
Section: Data Collectionmentioning
confidence: 99%
“…The mangrove ecosystem is an ideal habitat for spawning and feeding communities such as Crustacea, Gastropoda and Bivalvia (Azmi et al 2022;Isroni et al 2023;Mawardi et al 2023). Bivalves and crustaceans share similar habitats with similar characteristics in coastal areas covered by mangrove (Islamy and Hasan 2020;Setyadi et al 2021). Mangroves, characterized by their long roots, play an important role in coastal areas and serve as sediment protectors and habitats for a variety of coastal fauna (Spalding et al 2014;Hasan et al 2022;Hasan et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Mangrove forests are natural resources that play an important role in maintaining the balance between terrestrial and aquatic ecosystems [1] [2]. The mangrove ecosystem is an area that functions as a bridge between land and sea.…”
Section: Introductionmentioning
confidence: 99%